Vitamin D supplementation prior to in vitro fertilisation in women with polycystic ovary syndrome: a protocol of a multicentre randomised, double-blind, placebo-controlled clinical trial. Issue 12 (8th December 2020) - Hu, Kai-Lun; Gan, Kwanghann; Wang, Rui; Li, Wentao; Wu, Qiongfang; Zheng, Beihong; Zou, Libo; Zhang, Su; Liu, Yifeng; Wu, Yiqing; Chen, Ruixue; Cao, Wushuang; et al.
Abstract : Introduction: Polycystic ovary syndrome (PCOS) is one of the leading causes of female infertility, affecting around 5% of women of childbearing age in China. Vitamin D insufficiency is common in women with PCOS and is associated with lower live birth rates. However, evidence regarding the effectiveness of vitamin D supplementation in women with PCOS is inconclusive. This multicentre randomised, double-blinded, placebo-controlled trial aims to evaluate the effectiveness of vitamin D supplementation prior to in vitro fertilisation (IVF) on the live birth rate in women with PCOS. Methods and analysis: We plan to enrol women with PCOS scheduled for IVF. After informed consent, eligible participants will be randomised in a 1:1 ratio to receive oral capsules of 4000 IU vitamin D per day or placebo for around 12 weeks until the day of triggering. All IVF procedures will be carried out routinely in each centre. The primary outcome is live birth after the first embryo transfer. The primary analysis will be by intention-to-treat analysis. To demonstrate or refute that treatment with vitamin D results in a 10% higher live birth rate than treatment with placebo, we need to recruit 860 women (48% vs 38% difference, anticipating 10% loss to follow-up and non-compliance, significance level 0.05 and power 80%). Ethics and dissemination: This study has been approved by the Ethics Committee in Women's Hospital of Zhejiang University on 2 March 2020 (reference number: IRB-20200035-R). All participants will provide written informed consent before randomisation. The results of the study will be submitted to scientific conferences and a peer-reviewed journal. Trial registration number: NCT04082650 .